Stress Granules in the Anti-Cancer Medications Mechanism of Action: A Systematic Scoping Review - Asadi, Mohammad Reza; Moslehian, Marziyeh Sadat; Sabaie, Hani; Poornabi, Marziye; Ghasemi, Elham; Hassani, Mehdi; Hussen, Bashdar Mahmud; Taheri, Mohammad; Rezazadeh, Maryam (Frontiers in Oncology, 2021)
Stress granule (SG) formation is a well-known cellular mechanism for minimizing stress-related damage and increasing cell survival. In addition to playing a critical role in the stress response, SGs have emerged as critical mediators in human health. It seems logical that SGs play a key role in cancer cell formation, development, and metastasis. Recent studies have shown that many SG components contribute to the anti-cancer medications' responses through tumor-associated signaling pathways and other mechanisms. SG proteins are known for their involvement in the translation process, control of mRNA stability, and capacity to function in both the cytoplasm and nucleus. The current systematic review aimed to include all research on the impact of SGs on the mechanism of action of anti-cancer medications and was conducted using a six-stage methodological framework and the PRISMA guideline. Prior to October 2021, a systematic search of seven databases for eligible articles was performed. Following the review of the publications, the collected data were subjected to quantitative and qualitative analysis. Notably, Bortezomib, Sorafenib, Oxaliplatin, 5-fluorouracil, Cisplatin, and Doxorubicin accounted for the majority of the medications examined in the studies. Overall, this systematic scoping review attempts to demonstrate and give a complete overview of the function of SGs in the mechanism of action of anti-cancer medications by evaluating all research.